1989
DOI: 10.1007/bf00585620
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atrial natriuretic factor (ANF) on nicotinic acetylcholine receptor channels in bovine chromaffin cells

Abstract: Abstract. Bovine chromaffin cells have binding sites for rat atrial natriuretic factor (ANF), as demonstrated autoradiographically by using the ~2SI-labelled peptide. Patch-clamp recording revealed that ANF reduces acetylcholine (ACh)-induced membrane currents in chromaffin cells at physiological membrane potentials. The effect was dose-dependent with the ICs0 value being 5.2 pM ANF and the Hill coefficient close to 1. The channel block was absent at positive membrane potentials, indicating a non-competitive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This supports the interpretation of the involvement of the ANF-R, receptors and challenges the possibility of nonspecific ionic interactions with the nicotinic receptor ionophore complex. Indeed, as shown by Bormann et al . (1989), non-receptor-dependent inhibition of nicotinic currents by NPs occurs only at high peptide concentrations ( > 1 PM) .…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…This supports the interpretation of the involvement of the ANF-R, receptors and challenges the possibility of nonspecific ionic interactions with the nicotinic receptor ionophore complex. Indeed, as shown by Bormann et al . (1989), non-receptor-dependent inhibition of nicotinic currents by NPs occurs only at high peptide concentrations ( > 1 PM) .…”
Section: Discussionmentioning
confidence: 53%
“…This selective expression of the ANF-R,,, subtype is consistent with previously published distribution of this receptor in other species (Wilcox et al ., 1991 ;Féthière et al ., 1993) and with the major localization of CNP within the nervous system (Ueda et A ., 1991 ;Minamino et al ., 1993) . The micromolar IC 5 values for ANF inhibition of nicotinic currents previously reported by Bormann et al ( 1989) do not reflect normal physiological conditions . We therefore conducted patch-clamp studies to verify if CNP displayed current inhibition properties at nanomolar concentrations, in agreement with ANF-R,,, receptor affinities.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…ANP inhibits secretion from PC12 cells (Drewett el al., 1988); however, these cells differ in many respects from bovine chromaffin cells. Bormann et al (1989) found that ANP inhibited acetylcholine-induced currents in bovine chromaffin cells. This inhibitory effect of ANP was only seen at concentrations of ANP greater than those used here (> 1 p M ) .…”
Section: Resultsmentioning
confidence: 95%